Social defeat stress affects resident's clock gene and bdnf expression in the brain - Moravcová, Simona; Červená, Kateřina; Míková, Hana; Pačesová, Dominika; Pallag, Gergely; Novotný, Jiří; Bendová, Zdeňka (Stress (Amsterdam, Netherlands), 2021)
Social defeat stress affects behavior and changes the expression of the genes underlying neuronal plasticity in the brain. The circadian clock regulates most neuronal processes in the brain, which results in daily variations of complex behavior, and any disturbance in circadian clock oscillations increases the risk of mood and cognitive disbalance. In this study, we assessed the effect of acute and repeated social defeat stress on Per2 and Nr1d1 expression in prefrontal cortexes, hippocampi, pineal glands, olfactory bulbs, cerebella, and pituitary glands. We also evaluated the effect of our experimental setting on levels of Bdnf and plasma corticosterone, two markers widely used to asses the impact of stress on mammalian physiology. Our data show that single and repeated social defeat stress upregulates the expression of both clock genes and Bdnf in all brain structures, and corticosterone in the blood. While the general pattern of Bdnf upregulation suggests higher sensitivity in the intruder group, the clock genes are induced more significantly in residents, especially by repeated stress sessions. Our work thus suggests that the model of stress-induced anxiety and depression should consider a group of residents because, for some parameters, they may respond more distinctively than intruders.LAY SUMMARYThe resident/intruder experimental paradigm affects the expression of clock genes Per2, Nr1d1and Bdnf in the brain structures and plasma corticosterone level. The induction of clock genes is evident in both experimental groups; however, it is more marked in residents. Together with the significant increase in Bdnf levels in the majority of brain structures and plasma corticosterone in residents, our data suggest that in the model of social defeat stress, the utility of an experimental group of residents could be contributive.
Keywords: Animals; Social Defeat; Rats; corticosterone; Rats, Wistar; psychický stres; brain-derived neurotrophic factor; kortikosteron; Corticosterone; brain; mozek; rat; Clock genes; proteiny CLOCK; Brain; Brain-Derived Neurotrophic Factor; krysa rodu Rattus; mozkový neurotrofický faktor; Social Behavior; zvířata; sociální chování; social defeat stress; Stress, Psychological; sociální porážka; CLOCK Proteins; potkani Wistar